1991
DOI: 10.4315/0362-028x-54.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Effect of High Pressure CO2 Treatment on Foods Spiked with Listeria or Salmonella

Abstract: Studies were carried out to assess the use of high pressure CO2, treatment for controlling pathogenic microorganisms in model food systems. Listeria monocytogenes suspended in distilled water was completely killed after CO2 treatment at 6.18 MPa (61.2 atm) and 35°C for 2 h. Contrary to CO2 treatment, the use of N2 at these experimental conditions failed to exert bactericidal effect. High pressure CO2 treatment at 13.7 MPa (136.1 atm) and 35°C for 2 h was shown to effectively kill Salmonella in spiked chicken m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(82 citation statements)
references
References 0 publications
2
76
0
4
Order By: Relevance
“…7.8) Other approaches involving no flash pressure drop, using high-pressure COz treatment alone, have also been widely studied to provide the required lethal action on various kinds of microbes. 9 -17) For example, Kamihira et 15 ) From these investigations, most microbial cells appear to be sterilized mainly due to the inactivating effect of COz under pressure; this may be in conflict with the foregoing explanation of the sterilization mechanism for explosive decompression.…”
mentioning
confidence: 99%
“…7.8) Other approaches involving no flash pressure drop, using high-pressure COz treatment alone, have also been widely studied to provide the required lethal action on various kinds of microbes. 9 -17) For example, Kamihira et 15 ) From these investigations, most microbial cells appear to be sterilized mainly due to the inactivating effect of COz under pressure; this may be in conflict with the foregoing explanation of the sterilization mechanism for explosive decompression.…”
mentioning
confidence: 99%
“…Erkmen and Karaman (2001) observed that the exposure time required to achieve the same level of Salmonella inactivation was drastically reduced as the pressure during the inactivation increased. Complete inactivation of Salmonella was reported in egg yolk, 94-98% in chicken meat strips and limited inactivation in whole egg at a pressure of 13.7 MPa at 35 °C for 2 h (Wei et al, 1991). The variation in the results clearly indicates the complex nature of food systems.…”
Section: High Pressure Carbon Dioxide (Hpcd)mentioning
confidence: 97%
“…These reactive ionic species can then have an effect on the permeability of the cell membrane and properties of cell constituents. In addition, generation of carbonic acid (H 2 CO 3 ) in the water present in food products further results in a reduction in the pH of the food products enhancing the penetration of CO 2 (Wei et al, 1991). Studies involving the use of HPCD for the inactivation of S. Typhimurium (Kim et al, 2007;Erkmen and Karaman, 2001;Erkmen 2000;Wei et al, 1991) have clearly reported the microbial strain, pressure applied, pH of the medium, type of medium and temperature to be important factors for the inactivation.…”
Section: High Pressure Carbon Dioxide (Hpcd)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the most promising techniques for cold pasteurization and/or sterilization of liquid and solid materials, and is likely to replace or partially substitute currently and widely applied thermal processes (Spilimbergo and Bertucco, 2003). Over the past decades, many reports have demonstrated the substantial inactivation effect of carbonation under mild treatment conditions against various microorganisms in vegetative form, such as Escherichia coli (Dillow et al, 1999), Listeria monocytogenes (Wei et al, 1991), and Lactobacillus plantarum (Hong and Pyun., 1999). However, spores of various Bacillus species are metabolically dormant and are thus highly resistant to environmental stress factors (Ghosh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%